The Therapeutic Potential of Insulin Eye Drops in Neurotrophic Keratopathy: A Comprehensive Review - Roxana Scripcă; Sinziana Istrate; Emil Ungureanu; Ștefan Oprea; Nicoleta Anton; Madalina Boruga; Marius Alexandru Moga; Ancuța-Georgiana Onofrei (Biomedicines, 2025)
This review explores the potential role of topical insulin drops in corneal regeneration by analyzing the mechanism of action and clinical outcomes. Corneal integrity restoration is crucial for ocular surface healing. This review synthesizes the current literature on topical insulin for neurotrophic keratopathy (NK), highlighting its mechanism of action, therapeutic potential, and clinical outcomes. Recent studies report high rates of epithelial regeneration, suggesting that topical insulin may be an effective adjunct or alternative to conventional treatments. Further randomized controlled trials are needed to confirm its long-term efficacy and optimal dosing. Methods: Considering the limited regenerative capacity of the corneal epithelium in NK and the increasing interest in novel therapy, we review the existing literature to evaluate the role and extent of topical insulin’s contribution to corneal healing by applying the PICO framework, which allows for a clear and systematic approach to literature selection and evaluation. The literature search and study selection were conducted manually following PRISMA guidelines. Conclusions: Most of the studies resulting from the selection have small samples, and there is a lack of large, randomized clinical trials. The evidence reviewed in this study suggests that topical insulin is a promising therapy for promoting corneal healing in neurotrophic keratopathy. While clinical trials have demonstrated significant epithelial regeneration, optimal dosing and long-term safety require further investigation. Compared to conventional treatments such as autologous serum or growth factor therapy, insulin eye drops provide a cost-effective alternative. Additional research through controlled trials is needed to formulate standardized therapeutic protocols and verify long-term outcomes.